Effects of Gas Production on Acoustic Radiation Characteristics of Underwater Pyrotechnic Combustion. Issue 1 (March 2015) - Li, Jie; Guan, Hua; Song, Dongming; Wang, Qi; Du, Jun
In order to understand the effects of gaseous production on the acoustic radiation characteristics of underwater pyrotechnic combustion, the pyrotechnic combustion pressure-time curves are plotted using a closed bomb and then maximum pressure is used to calculate the quantity of gaseous products. The results show that among the four pyrotechnic compositions with different gas productions, overall sound pressure level (OASPL) and 1/3 octave band sound pressure level (SPL) in composition #4 which has the highest nozzle gas flow, shortest period of bubble formation and largest maximum bubble diameter, reached 165.1 dB and 163 dB respectively, which were 6 dB and 10 dB higher than the corresponding minimum values. During underwater pyrotechnic combustion, bubbles were formed at the nozzle of the combustion device and thus generated low-frequency noise. The increased gas production resulted in a shorter bubble formation period, a larger number of bubbles, and larger bubble diameter, which destabilize the fluid during bubble formation, improve the prone of bubbles to coalescence and breakup, and increase the sound pressure level.